Development of a multi-media system for kinesiological evaluation of swimming by experts in any pool - Soons, B.; Colman, V.; Persyn, U. (Biomechanics and Medicine in Swimming X, 2006)
A long term strategy is presented to develop a kinesiological evaluation System in breaststroke, useable by any expert, based on movement variables relevant for performance. Because relations were found between physical characteristics as well as velocity Variation of the centre of mass, on the one hand, and body cambering and waving, on the other hand, these two undulating characteristics were chosen as style criterions. For the different style groups, and in women and men separately, a series of movement variables in various phases of the stroke cycle were also relevant for performance. Movement deviations can be specified by overlaying average stick figures of the most corresponding style group on video instants, but also by refer-ring to the average stick figures of the gender group.